DAMPAK METODE PEMBELAJARAN BERBASIS PROYEK (PjBL) TERHADAP PRESTASI BELAJAR DALAM MATA KULIAH INVENTORY CONTROL - Rarasati, Niken; Kholijah, Gusmi; Tasmara, Annida (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
One of learning method that can provide practical experience for students can be made in the form of a project. Project-based learning can be carried out in the Inventory Control course, this is because the inventory course has a course description for decision making in optimizing profits with inventory management. Project-based learning can also provide soft skills for students, including; leadership ability, responsibility for the given project, cooperation, good communication between students and the community and independence. Project-based learning research in the Inventory Control course is carried out in three stages, namely: preparation, implementation and evaluation. In the preparation stage, the research team discussed and prepared research outputs such as Course Learning Outcomes, Lecture Syllabus and Contract, Semester Learning Plan, Student Project Assignment Plan, and Learning Outcome Assessment Sheet. Based on the results of the analysis, it was found that 98.61% of learning outcomes were successfully achieved by implementing the project in the Inventory Control Course